New Zealand : Financial Sector Assessment Program: Technical Note-Fund Management-Regulation, Supervision, and Systemic Risk Monitoring. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2017)
This Technical Note presents an assessment of Regulation, Supervision and Systemic Risk Monitoring in New Zealand. The overall regulatory framework for asset management is well developed, but would benefit from some enhancements to prevent the buildup of risks. The provision of custody services does not require a license in New Zealand, and custodians therefore fall outside the direct supervision of the Financial Markets Authority (FMA). They are neither subject to prudential requirements nor to ongoing supervision by any other authority. Given that custodians perform key functions regarding safeguarding investors' assets, the government should require that these entities be licensed and subject to ongoing supervision by the FMA.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet